Short term statin treatment improves survival and differentially regulates macrophage-mediated responses to Staphylococcus aureus - Burns, Erin M. (Curr Pharm Biotechnol, 2013)
Staphylococcus aureus is the most prevalent etiologic agent of sepsis. Statins, primarily prescribed for their cholesterol-lowering capabilities, may be beneficial for treating sepsis due to their anti-inflammatory properties. This study examined the effect of low dose, short term simvastatin pretreatment in conjunction with antibiotic treatment on host survival and demonstrated that pretreatment with simvastatin increased survival of C57BL/6 mice in response to S. aureus infection. In vitro studies revealed that short term simvastatin pretreatment did not reduce S. aureus-stimulated expression of surface proteins necessary for macrophage presentation of antigen to T cells, such as MHC Class II and co-stimulatory molecules CD80 and CD86, but did reduce both basal and S. aureus-stimulated levels of C5aR. Additionally, this work demonstrated the ability of simvastatin to dampen macrophage responses initiated not only by bacteria directly but by membrane vesicles shed in response to infection, revealing a new mechanism of immune modulation by statins. These data demonstrate the ability of short term simvastatin pretreatment to modulate immune responses and identify new insights into the underlying mechanisms of the anti-inflammatory properties of simvastatin that may decrease the pathophysiological effects leading to sepsis.